Seized by seduction - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Protectors., 2017)
From the moment his eyes meet hers across the crime-scene tape, ex-con turned bodyguard Quasar Patterson knows he has to see mysterious Dr. Randi Fuller again. She's a renowned psychic investigator who can foresee danger for others, but not for herself. That makes Quasar doubly determined to watch over her - the closer, the better- as she's drawn into a dangerous gang rivalry.